Therapeutic evaluation of Martynia annua derived carbon dots in epileptic Drosophila model - Megha B. Abbigeri; Muskan Khan; Bothe Thokchom; Sapam Riches Singh; Santosh Mallikarjun Bhavi; Sudheendra Rao Kulkarni; B. P. Harini; G. Vidya Sagar Reddy; Chandramohan Govindasamy; Khalid M. Almutairi; Yarajarla Ramesh Babu (Scientific Reports)
Abstract This study investigates the synthesis and characterization of Carbon dots (MA-CDs) derived from the aqueous extract of Martynia annua and examining their potential effects in an epilepsy model Drosophila melanogaster. Phytochemical analysis confirmed the presence of saponin, terpeniods, and flavanoids in the leaf extract, which facilitated the green synthesis of MA-CDs. Physicochemical characterization revealed an absorbance peak at 326 nm, the mean size of the particle was 3.17 ± 0.16 nm, and moderate stability (−1.6 mV). To assess the therapeutic potential of MA-CDs alongside the antiepileptic drug Carbamazepine (CBZ), we conducted behavioral and cognitive assays in para bang senseless (parabss1) mutants of Drosophila, a model organism for epilepsy. Seizures induced by vortex and heat shock were significantly mitigated in a dose-dependent manner in flies treated with both MA-CDs and CBZ. However, higher doses of CBZ and MA-CDs increased the climbing ability of the flies. In cognitive assays, CBZ at higher doses improved memory and learning in mutant flies, while MA-CDs also showed significant impact. MA-CDs were consumed at a higher rate than CBZ when incorporated into food. The green synthesized MA-CDs at its higher concentration has garnered its positive effect on the mutants along with the CBZ antiepileptic drug which also has shown its positive effects when different concentration of them were treated to the mutants.